2020
DOI: 10.1183/16000617.0042-2020
|View full text |Cite
|
Sign up to set email alerts
|

Birt–Hogg–Dubé syndrome

Abstract: Birt–Hogg–Dubé syndrome (BHD) is a rare inherited autosomal dominant disorder caused by germline mutations in the tumour suppressor gene FLCN, encoding the protein folliculin. Its clinical expression typically includes multiple pulmonary cysts, recurrent spontaneous pneumothoraces, cutaneous fibrofolliculomas and renal tumours of various histological types. BHD has no sex predilection and tends to manifest in the third or fourth decade of life. Multiple bilateral pulmonary cysts are found on chest computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 130 publications
1
65
0
10
Order By: Relevance
“…with the mammalian target of rapamycin(mTOR) and adenosine monophosphate-activated protein kinase (AMPK) signaling pathways [2][3][4][5]. Over 600 families with BHD have been reported worldwide in the past 40 years, mainly Caucasians in Europe and USA.…”
mentioning
confidence: 99%
“…with the mammalian target of rapamycin(mTOR) and adenosine monophosphate-activated protein kinase (AMPK) signaling pathways [2][3][4][5]. Over 600 families with BHD have been reported worldwide in the past 40 years, mainly Caucasians in Europe and USA.…”
mentioning
confidence: 99%
“…Due to the high prevalence of lung cysts in adult patients with BHDS, spontaneous pneumothorax has been found to be a common presentation 3 . In our study, 71% of con rmed patients had at least one episode of pneumothorax and nearly 85% of them had a family history of pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent study revealed that the prevalence of renal tumors in patients with BHD was 34% with a mean age at diagnosis of approximately 50 years 33 . Chromophobe renal carcinoma was the most common histological type of renal cancer, followed by hybrid oncocytic/chromophobe tumor 3,7 . Similar ndings were reported in a recent largest study including 312 Japanese cases from 120 different families 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations